Evolutionary Institutionalism. Sources, history and contemporary relevance of The Association for Evolutionary Economics - AFEE - Wolfram Elsner (Intervention. European Journal of Economics and Economic Policies, 2011)
First paragraph: Evolutionary-institutional economics is more than 110 years old. It started with Thorstein B. Veblen's fundamental criticism, put forward in a bulk of papers and books from the 1880s on, of the then just-established neo-classical economic mainstream. Veblen had worked empirically, and established on theoretical, methodological, and philosophical levels a new type of economics. He pointed out the simplistic, equilibrium-oriented, over-optim(al)istic, and teleological view that had emerged from the Scottish Enlightenment school to the classical economists from Adam Smith on (the fable of the bees, the natural price and invisible hand metaphors, etc.), even though the Scottish Enlightenment had developed an early understanding of what today would be termed complex emergence, already pointing beyond a simple mechanical analogy. In his view, their naïve teleological inclinations had paved the way for the overtly simplistic, autistic, rigid, equilibrium- and optimality-based neoclassical modelling of a perfect-market economy which he considered straightforwardly outmoded, ideological, counter-productive, and dangerous.
Keywords: 330